Bread making - Inskeep, Helen C. (My University, 1906)
Introduction: It may be said that there is no other food, with the single exception of milk, which is so universally used as is bread. By bread we may include any food made from flour or meal by moistening, kneading and baking. According to early historical records bread has existed in some form or other for centuries past. It is true that the bread used by the Indians which inhabited our country in the early days, did not, nor does that used by the uncivilized man of this age very closely resemble that used by the civilized man of this age. Yet they knew no other so were perfectly contented with what they had and it filled the same place to them then which our bread now fills for us. And because of its importance in the diet much more care should be taken with it than is usually done. Again considering it from a dietetic standpoint it is the most nearly perfect food of any of the ordinary foods unless it is milk. In many places where other articles of food are difficult to obtain bread is almost their only food, in this case it usually consists of ground wheat or millet moistened in water and baked. Though it seems hardly possible it is nevertheless true that the civilization of any district may be judged by the bread made in that district. Primitive man had the very most simple bread making methods, while from time to time new methods have been discovered and improvements are constantly being made as civilization advances, in the process and results of bread making and bread baking. Bread has a great value as an economic food being one of the cheapest if not the cheapest way of supplying the proper nourishment to the body.
Citation: Inskeep, Helen C. Bread making. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Baking; Bread; Theses